2015
DOI: 10.1139/cjce-2014-0078
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual approach to track design changes within a multi-disciplinary building information modeling environment

Abstract: Successful management of design changes is critical for the efficient delivery of construction projects. Building information modeling (BIM) is envisioned to play an important role in integrating design, construction and facility management processes through coordinated changes throughout the project life-cycle. BIM currently provides significant benefits in coordinating changes across different views in a single model, and identifying conflicts between different discipline-specific models. However, current BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Meanwhile, other preeminent research themes in this category include: RC2.5 -"structural analysis and design" (Bosché, Guenet 2014;Ham, Golparvar-Fard 2015;Lee et al 2012a;Marzouk, Abdelaty 2014b); RC2.6 -"building rating systems and assessments" (Basbagill et al 2013;Oti et al 2016;Ryu, Park 2016); RC2.7 -"tracking of design changes and errors" (Dong et al 2014;Lee et al 2015a;Pilehchian et al 2015); RC2.8 -"daylighting profiling" (Welle et al 2012), and RC2.9 -"design validation and coordination" (Gimenez et al 2016;Kim, Jeon 2012;Kim, Yu 2016b;Lee et al 2012b;Shin, Cho 2015). Meanwhile, a bibliometric analysis of this category reveals more BIM publications in areas such as RC2.5 -"structural analysis and design" with 13 articles and RC2.3 -"building envelope, cost, and energy performance" with 12 BIM articles.…”
Section: Building Design and Energy Conformance (Rc2)mentioning
confidence: 99%
“…Meanwhile, other preeminent research themes in this category include: RC2.5 -"structural analysis and design" (Bosché, Guenet 2014;Ham, Golparvar-Fard 2015;Lee et al 2012a;Marzouk, Abdelaty 2014b); RC2.6 -"building rating systems and assessments" (Basbagill et al 2013;Oti et al 2016;Ryu, Park 2016); RC2.7 -"tracking of design changes and errors" (Dong et al 2014;Lee et al 2015a;Pilehchian et al 2015); RC2.8 -"daylighting profiling" (Welle et al 2012), and RC2.9 -"design validation and coordination" (Gimenez et al 2016;Kim, Jeon 2012;Kim, Yu 2016b;Lee et al 2012b;Shin, Cho 2015). Meanwhile, a bibliometric analysis of this category reveals more BIM publications in areas such as RC2.5 -"structural analysis and design" with 13 articles and RC2.3 -"building envelope, cost, and energy performance" with 12 BIM articles.…”
Section: Building Design and Energy Conformance (Rc2)mentioning
confidence: 99%
“…Previous research works related to BIM for construction claim management are as follows. Design change tracking encompassed creating an add-in utilizing Revit.NET API [15] and using Solibri Model Checker [10]. The model checker has also been extended for specific purposes such as spatial requirement checking [29] and regulation compliance checking [30].…”
Section: Literature Review On Bim For Construction Change Order Managmentioning
confidence: 99%
“…Recent studies show that advanced technologies played an essential role in improving the traditional practice. The graphical approach for evaluating the impacts of change orders such as Building Information Modeling (BIM) is still limited even though a number of previous studies confirmed that BIM can assist in tracking design changes across multi-disciplinary [10], contributing to successful construction projects [11].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [22] proposed a framework for measuring the impacts of Change Orders in construction projects and used it as a pre-risk assessment tool. Different researchers used Building Information Modelling for the management of design changes [23,24]. Isaac and Navon [25] developed a model that facilitates an automatic identification of the possible consequences of changes when they are first proposed, before their implementation in the design and planning of the project.…”
Section: Introductionmentioning
confidence: 99%